FAKTOR - FAKTOR YANG MEMPENGARUHIKETIDAKPATUHAN WAJIB PAJAK DI WILAYAH KECAMATAN RUNGKUT SURABAYA - Rachmawati, Elita; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This researchanalyzes some factors which influence the non-compliance individual taxpayerin Rungkut district Surabaya, thevariables which are used inthis research are the knowledgeof taxation, tax rates, tax audit, service quality, service effectiveness, the condition of economy, the prevailing law, the respond of governmentandnon-compliancetaxpayer.This research usestaxpayersin the Rungkut district as research samples.The samples are 50respondents, themultiple linear regression is used as the analysis, this researchgenerates theR square value0.845 which meansthatthe knowledgeof taxation,tax rates, tax audit, service quality, service effectiveness, economy, law, the respond of the government to the non-compliance taxpayers variables are 84.5%. The F test has obtainedsignificantvalue0.000. Thus, it can be said thatall independent variablessimultaneously have influence to thenon-compliancetaxpayers.It has been obtained from the t testthat partiallyknowledge oftaxation, tax rates, service quality, the condition of economyandthe prevailinglaw influence the non-compliance taxpayers whereas tax audit, the effectiveness of services, andthe respond of thegovernment variable partially do nothave any influence tothe non-compliance taxpayers.Keywords:Tax rate, Service Quality, the Condition of Economy, the Prevailing Law, the non-compliance taxpayers